Family assistants’ living and working conditions and their interaction with patient and family caregiver variables: A study protocol - Simeone, Silvio; Pucciarelli, Gianluca; Dal Lago, Elisa; Botti, Stefano; Gargiulo, Gianpaolo; Vellone, Ercole; Alvaro, Rosaria (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: The progressive and constant aging of the global population together with the economy crises and the social variations within family contexts increasingly leads to the use of external resources (Home Care Workers, HCWs) for health care within one’s own family of origin. Purpose of the study is to describe Italian Home Care Workers’ (HCWs) living and working conditions and understand the interactions with outcomes of the patients and informal caregiver. Methods: Observational study with cross sectional design to evaluate the interaction of HCWs without specific training on patients and informal caregivers’ outcomes. Results: understand Italian HCWs’ condition and interaction between these conditions and outcomes of patients and informal caregiver. Conclusions: understanding how HCWs’ conditions can affect outcome about patient and informal caregivers, represents a fundamental step in order to increase QoL of these families.